Genetics, Mechanisms and Deployment of Brown Planthopper Resistance Genes in Rice. (4th March 2022) - Mishra, A.; Barik, S. R.; Pandit, E.; Yadav, S. S.; Das, S. R.; Pradhan, S. K.
Abstract: Among the rice insects, brown planthopper (BPH), ( Nilaparvata lugens Stål) is a monophagous migratory phloem-sucking insect causing severe loss in Asiatic countries. High nitrogen and willful insecticide application coupled with an increase in temperature have created havoc by this pest during the last few years in certain parts of India, Indonesia, China, Japan, Taiwan, Vietnam, and the Philippines. Though chemical control measures are advocated to mitigate this insect, yet, the incorporation of host-plant resistance factor is the preferred approach to manage this insect attack owing to the high cost of chemical control and adverse effects on the environment. To date, more than 40 major resistance genes and 22 minor genes or quantitative trait loci (QTLs) are identified. Cloning of 11 BPH resistance genes has been completed to date. Majority of the cloned genes produced coiled-coil nucleotide-binding and leucine-rich repeat protein for the defense response in the host plant. Salicylic acid, jasmonic acid, ethylene, mitogen-activated protein kinases, Ca 2+, OsRac1, and other signaling molecules play a definite role in the defense response. Signal transduction may lead to sieve tube sealing, production of metabolites, and induction of proteinase inhibitor for defense response against BPH attack. Plants have intrinsic mechanisms for recognition of damage-associated and herbivore-associated molecular patterns and elicitors for host defense response. This review provides an update on the sources of resistance, identification of resistance genes, gene maps, (QTL) detection, cloning, insights into the molecular mechanisms of resistance, and deployment of resistance genes for durable and broad-spectrum resistance in the cultivars against BPH.